2002
DOI: 10.1164/ajrccm.165.6.2003166
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Continuous Positive Airway Pressure in Mild Obstructive Sleep Apnea

Abstract: A common clinical dilemma faced by sleep physicians is in deciding the level of severity at which patients with obstructive sleep apnea (OSA) should be treated. There is particular uncertainty about the need for, and the effectiveness of, treatment in mild cases. To help define the role of nasal continuous positive airway pressure (CPAP) treatment in mild OSA we undertook a randomized controlled cross-over trial of CPAP in patients with an apnea- hypopnea index (AHI) of 5 - 30 (mean, 12.9 +/- 6.3 SD). Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
202
3
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(216 citation statements)
references
References 36 publications
3
202
3
6
Order By: Relevance
“…150 In addition, short-term CPAP treatment in patients with well-controlled hypertension did not elicit any BP improvement. 151 Recent studies have more often been placebo controlled, [152][153][154] comparing CPAP with either placebo pills or with sham CPAP. BP reduction is either modest or absent in normotensive subjects but may be more evident in hypertensives.…”
Section: Treatment Of Osa: Effects On Hypertensionmentioning
confidence: 99%
“…150 In addition, short-term CPAP treatment in patients with well-controlled hypertension did not elicit any BP improvement. 151 Recent studies have more often been placebo controlled, [152][153][154] comparing CPAP with either placebo pills or with sham CPAP. BP reduction is either modest or absent in normotensive subjects but may be more evident in hypertensives.…”
Section: Treatment Of Osa: Effects On Hypertensionmentioning
confidence: 99%
“…Similarly, Bardwell et al (2003) found that depressive symptoms accounted for approximately 40% of the variance in fatigue reported in OSA patients after apnoea severity was taken into account [25]. In addition to these findings, levels of both depressive symptoms and fatigue have been found to be attenuated by CPAP treatment [36][37], further supporting the existence of an interaction between these symptoms within sleep disturbed populations.…”
Section: Discussionmentioning
confidence: 87%
“…Although oral placebo has been used as a control group in several randomized controlled CPAP trials (49)(50)(51)(52)(53)(54)(55), an alternative, commonly used approach is sham-CPAP, a specially designed CPAP device with minimal and clinically ineffective airway pressure. We chose to use oral placebo rather than sham-CPAP in the control group for several reasons.…”
Section: Original Articlementioning
confidence: 99%